A proteomic profile of postpartum cervical repair in mice. (January 2018) - Stanley, Robert Lee; Ohashi, Takako; Gordon, Jacob; Mowa, Chishimba Nathan
Abstract : A timely and complete uterine cervical tissue repair postpartum is of necessity to prevent obstetrical complications, such as cervicitis, ectropion, hemorrhage, repeated miscarriages or abortions and possibly preterm labor and malignancies. We recently characterized the morphological alterations, as well as changes in angiogenic expression profile in a mice uterine cervix during the immediate postpartum period. Here, we build on this previous study using a proteomic analysis to profile postpartum tissue changes in mice cervix during the same period, the first 48 h of postpartum. The current proteomics data reveal a variable expression of several intermediate filaments, cytoskeletal modulators and proteins with immune and/or wound-healing properties. We conclude that postpartum cervical repair involves a rapid and tightly regulated balance between a host of biological factors, notably between anti- and pro-inflammatory factors, executed by the M1 and M2 macrophage cells, as revealed by proteomics and verified by confocal immunofluorescence. Future studies will assess the suitability of some of the key proteins identified in this study as potential markers for determining the phase of postpartum cervical repair in obstetrical complications, such as cervical lacerations.